Early Kiwifruit Decline: A Soil-Borne Disease Syndrome or a Climate Change Effect on Plant–Soil Relations? - Bardi, Laura (Frontiers in Agronomy, 2020)
Early kiwifruit decline is a physiological disorder reported for the first time in New Zealand following a cyclone that caused a heavy and prolonged flooding of kiwifruit orchards. Following studies on kiwifruit vine physiology and anatomy demonstrated that this plant has a significant water demand but is also extremely sensible to root waterlogging and soil anoxic conditions. Pathogenic microorganisms were sometimes identified in soil and root samples of declining plants, but they were not considered the primary cause of kiwifruit decline, and their presence in roots was considered a consequence of waterlogging and plant weakening. Agronomic practices have been developed and adopted to deliver water in amounts adequate to plant needs, but avoiding excess and stagnation in the soil, and to improve soil aeration. However, in recent years, early decline has seen worldwide spread, affecting even orchards in which waterlogging is prevented or is only occasionally caused by intense local rainfall. A global overview of the knowledge on botanical, physiological, and ecological traits of kiwifruit, along with the examination of phenomena concomitant to early decline appearance, can help to identify the causes and the possible actions to prevent its occurrence. Some assumptions and possible solution attempts are proposed.